Deep Phenotyping of T-Cells Derived From the Aneurysm Wall in a Pediatric Case of Subarachnoid Hemorrhage - Moschetti, Giorgia; Vasco, Chiara; Clemente, Francesca; Galeota, Eugenia; Carbonara, Marco; Pluderi, Mauro; Locatelli, Marco; Stocchetti, Nino; Abrignani, Sergio; Zanier, Elisa R; Ortolano, Fabrizio; Zoerle, Tommaso; et al. (Frontiers in Immunology, 2022)
Intracranial aneurysms (IAs) are very rare in children, and the characteristics of the T-cells in the IA wall are largely unknown. A comatose 7-years-old child was admitted to our center because of a subarachnoid hemorrhage due to a ruptured giant aneurysm of the right middle cerebral artery. Two days after the aneurysm clipping the patient was fully awake with left hemiparesis. T-cells from the IA wall and from peripheral blood of this patient were analyzed by multi-dimensional flow cytometry. Unbiased analysis, based on the use of FlowSOM clustering and dimensionality reduction technique UMAP, indicated that there was virtually no overlap between circulating and tissue-infiltrating T-cells. Thus, naïve T-cells and CXCR3+Th1- and CCR6+Th17-cells were largely restricted to peripheral blood. The unique T-cell clusters from the IA wall expressed insteads high levels of CCR5, Granzyme zmB and CD69, but had down-regulated CD27, displaying thus characteristics of cytotoxic and tissue-resident effector cells. Low KI67 expression indicated that they were nevertheless in a resting state. Among regulatory T-cells FOXP3+Tregs were present at normal frequencies, while Eomes+Tr1-like cells were strongly enriched in the IA wall. Finally, analysis of cytokine producing capacities unveiled that the IA wall contained poly-functional T-cells, which expressed predominantly IFN- TNF and IL-2, and in particular CD4+T-cells expressed also CD40L, as well as some IL-17, GM-CSF and IL-10. Finally, T-cells from the IA wall produced predominantly IFN- TNF and IL-2, but also some IL-17, GM-CSF and IL-10This report provides to our knowledge the first detailed characterization of the human T-cell compartment in the IA wall.